The constant change of EU consumer law: The real deal or just an illusion? - Mišćenić Emilia (Anali Pravnog Fakulteta u Beogradu)
EU consumer law is in a process of constant change. Over the past several decades EU consumer law has gone through many changes, reaffirming the statement by Greek philosopher Heraclitus: the only constant is change (Panta Rhei). This paper emphasizes the transformative nature of EU consumer law and its constant changes. Firstly, the paper addresses the changes in legal grounds and competences, as the roots of EU consumer law. Secondly, it presents the changes of the levels of harmonization and their impact on EU consumer directives and the national laws of the Member States. It continues by observing the impact of the CJEU's uniform and autonomous interpretation on the national case law of the Member States and consumer law enforcement. In conclusion, the paper accentuates the role of the transparency requirements and information duties in online 'business-to-consumer' (B2C) transactions as fundamental aspects affecting the future of EU consumer law.